2015
DOI: 10.1111/jph.12370
|View full text |Cite
|
Sign up to set email alerts
|

Defence‐Related Enzymes in Soybean Resistance to Target Spot

Abstract: Target spot, caused by the fungus Corynespora cassiicola, has become a serious foliar disease in soybean production in the Brazilian Cerrado. Information in the literature regarding the biochemical defence responses of soybean to C. cassiicola infection is rare. Therefore, the objective of this study was to determine the biochemical features associated with soybean resistance to target spot. The activities of chitinases (CHI), b-1-3-glucanases (GLU), phenylalanine ammonia-lyases (PAL), peroxidases (POX), polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 48 publications
3
46
0
1
Order By: Relevance
“…A total of ten soybean seeds from cultivars TMG 132 and Fundacep 59, considered as susceptible and resistant to target spot, respectively (Fortunato et al. ,b), were sown into two‐L plastic pots (Ecovaso, Jaguariuna, SP, Brazil) containing 2 kg of Tropstrato ® (Vida Verde, Mogi Mirim, SP, Brazil) substrate composed of a 1 : 1 : 1 mixture of pine bark, peat and expanded vermiculite. Five days after seedlings emergence, each pot was thinned to two seedlings.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of ten soybean seeds from cultivars TMG 132 and Fundacep 59, considered as susceptible and resistant to target spot, respectively (Fortunato et al. ,b), were sown into two‐L plastic pots (Ecovaso, Jaguariuna, SP, Brazil) containing 2 kg of Tropstrato ® (Vida Verde, Mogi Mirim, SP, Brazil) substrate composed of a 1 : 1 : 1 mixture of pine bark, peat and expanded vermiculite. Five days after seedlings emergence, each pot was thinned to two seedlings.…”
Section: Methodsmentioning
confidence: 99%
“…; Fortunato et al. ,b). The necrotic lesions occasionally are large and coalesce, which can cause premature defoliation of the infected plants grown under favourable climatic conditions such as intense rainfall and high temperatures (Sinclair ; Godoy et al.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Enhanced production of fl avonoids in wheat leaves reduced incidence of blast caused by Pyricularia oryzae . Fortunato et al (2015) found that higher activity of total soluble phenolics and ligninthioglycolic acid derivatives in leaves of soybean plants supplied with silicon led to reduced incidence of target spot (Corynespora cassiicola). Regarding the perennial ryegrass-Magnaporthe oryzae interaction, Rahman et al (2015) found that several phenolic acids, including chlorogenic acid and fl avonoids, and relative levels of genes encoding phenylalanine ammonia lyase and lipoxygenase were signifi cantly increased in silicon-amended plants compared with non-amended control plants.…”
Section: Antifungal Compoundsmentioning
confidence: 99%